PERTUMBUHAN CABUTAN ANAKAN ALAM NYATOH (Palaquium sp.) SETELAH DISIMPAN PADA WADAH YANG BERBEDA - Porombi, Sulfriana; Umar, Husain; Taha, Irmasari (Universitas Tadulako, 2017)
The natural regeneration withdraw of nyatoh (Palaquium sp.) is a regeneration that withdrawn around the mother tree at natural forest and one of the multiple instruments that can be used. Therefore, the preparation process of natural regeneration that carried from the withdrawal place to the seedling place needs a special treatmentproses persiapan anakan alam yang dibawa dari tempat pencabutan ke persemaian memerlukan adanya perlakuan khusus yaitu pro it is packing by using some kinds of storage places. The objective of the research was to find out the good storage places for the withdraw of natural regeneration of nyatoh (Palaquium sp.) that used from withdrawal place to seedling place. The research used Complete Randomized Design that consisted of 5 treatments, they were (P1) Stem of banana bunch, (P2) gunny sack, (P3) Newspaper, (P4) Carton that layered by transparant plastic, (P5) coconut fiber, with 3 times repititions and each repitition consisted of i natural regeneration. The observed parameter involved height increase, stem diameter increase, and leaf number increase. The five storage places that triedwere good to be used bacause of their abilities to defend the humidity of withdrawal to be well remain for 24 hours. The result of the research showed that the growth of withdrawal of nyatoh (Palaquium sp.) natural regeneration after storaged on different place had unreal influence to the three observation paranmeters. From the three observation parameters, they were the average of height increase, the average of diameter increase, and the average of leaf number increase, the influence of given treatments stated consistent of each treatment. Which the result of the three parameters in a series were the stem banana bunch (P1) 2.32 cm, 0.47 mm, 2.37 sheets, gunny sack (P2) 2.03 cm, 0.39 mm, 2 sheets, Newspaper (P3) 1.91 cm, 0.34 mm, 1.75 sheets, Carton that layered by transparant plastic (P4) 2.11 cm, 0.43 mm, 2.25 sheets, and Coconut fiber (P5) 2.01 cm, 0.37 mm, and 1.75sheets. Keywords: storage place, natural regeneration withdraw, nyatoh